A study on the effectiveness of the promotional activities done by SBBU SDN BHD / Shahrizal Soteri @ Sotri - Soteri @ Sotri, Shahrizal (2004)
The purpose of this project is in analyzing the effectiveness of promotional activities done by SBBU SDN BHD at Plaza Angsana. The research was carried out using questionnaire distributed to the selected respondents by simple random sampling. Data then are analyzed using SPSS (Statistical Package for Social Science) software version 10.0. Data are analyzed using frequency and cross tabulation of descriptive analysis. The Chi-Square test is used to test the statistical significance of the observed association in a cross tabulation. Its assist us in determining whether a systematic association exists between the two variables. The principal finding, through the Chi-square testing, that most of the respondents are agreeing that promotional done by SBBU SDN BHD in promoting Plaza Angsana to their target market are effectively done. But there are certain areas that promotional activities done by SBBU SDN BHD are not quite effectively especially in banners promotion. Thus, actions and strategy must be planned on the criterion and also from other factors other than customer satisfaction.